Effects of 10 min vs. 20 min passive rest after warm-up on 100 m freestyle time-trial performance: A randomized crossover study - Neiva, H. P.; Marques, M. C.; Barbosa, T. M.; Izquierdo, M.; Viana, J. L.; Marinho, D. A. (Journal of Science and Medicine in Sport, 2017)
Objectives The aim of this study was to compare the effect of 10 min vs. 20 min passive rest post warm-up on performance in a 100 m freestyle time-trial. Design Randomized crossover. Methods Eleven competitive male swimmers performed two experimental trials on different days, consisting of 100 m freestyle time-trials following 10 min or 20 min passive rest after a standard 1200 m warm-up. Performance (time-trial), biomechanical (stroke length, stroke frequency, stroke index, propelling efficiency), physiological (blood lactate concentrations, heart rate, core and tympanic temperature), and psychophysiological (perceived effort) variables were assessed during both trials. Results Time-trial performance was faster after 10 min as opposed to 20 min passive rest (58.41 ± 1.99 s vs. 59.06 ± 1.86, p < 0.01). This was supported by strong effect sizes (d = 0.99) and the qualitative indication of "likely" positive effects. Heart rate before the time-trial was also higher after 10 min passive rest (89 ± 12 bpm vs. 82 ± 13 bpm; p < 0.01). Furthermore, net core temperature and oxygen uptake values before the time-trial were substantially lower after 20 min passive rest. Conclusions These data suggest that the 10 min post warm-up passive rest enhances 100 m freestyle performance when compared to a 20 min period. An improvement that appears to be mediated by the combined effects of a shorter post warm-up period on core temperature, heart rate and oxygen uptake.